PENTINGNYA ESQ (EMOSIONAL DAN SPIRITUAL QUESTION) BAGI MAHASISWA DALAM MANAJEMEN KONFLIK - Jon Iskandar Bahari (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
Results of research psychologists concluded that the success and the success of someone living in the strongly supported by emotional intelligence (EQ-80%), while the role of the Intellectual Intelligence (IQ) only 20% only. Which turned out to be its Center IQ and EQ is Spiritual intelligence (SQ), so it is believed that the decisive success and the SQ of the success of a person. In this case the IQ and EQ would be able to function properly/Effectively if controlled by the SQ. A heart enable our values the most in, changing it from something that we think is becoming something that we went through. Heart knows things that cannot be known by the mind. The heart is the source of courage and zeal, integrity and commitment. The heart is the source of energy and a feeling of depth that demands we learn, create, lead and serve. The supervisor will be the conscience of man against what should be accomplished and what to do, meaning that every human being has actually has a Heart as the accompanying Radar.